Predictions of the Compressible Fluid Model and its Comparison to Experimental Measurements of Q Factors and Flexural Resonance Frequencies for Microcantilevers - HEGNER, MARTIN (My University, 2012)
The qualitative agreement between experimental measurements of the 𝑄 factors and flexural resonance frequencies in air of microcantilevers and calculations based on the compressible fluid model of Van Eysden and Sader (2009) is presented. The 𝑄 factors and resonance frequencies observed on two sets of cantilever arrays were slightly lower than those predicted by the model. This is attributed to the individual design and geometry of the microfabricated hinged end of the cantilever beams in the array.
PUBLISHED
Inverse behaviour of Quality factors observed in higher modes in the gas phase
Keywords: 𝑄 factors; 𝑄 factors; Nanoscience & Materials